The chemokine CCL28 is elevated in the serum of patients with celiac disease and decreased after treatment - Rashidiani, Shima (Am J Clin Exp Immunol, 2017)
Accumulating evidence show that many inflammatory cytokines are involved in pathophysiology of celiac disease (CD). CCL28 known as mucosa associate epithelial chemokine (MEC) is produced by mucosa and chemoattracts IgA-producing B cells into the mucosa. However, its levels in patients with CD have not yet been elucidated. CCL28 levels and anti-tTTG (IgA) were detected in the serum of 28 new cases of CD, 32 cases of treated patents and 32 normal individuals by Elisa. Moreover, the effect of gluten on intestinal cells, Caco-2, was examined by RT-PCR. Our data show that (i) the levels of CCL28 is significantly higher in patients with CD than normal individuals, (ii) CCL28 levels is reduced in patients with CD who had gluten-free diets. Accordingly, we observed that CCL28 expression is upregulated in a dose-dependent manner when the Caco-2 cells were cultured in the presence of gluten. In conclusion, gluten enhances CCL28 expression and that CCL28 could be a novel biomarker for diagnosis and following up the patients with CD. However, further investigation in a larger number of patients is required.